(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The emergence of new challenges and threats in the modern world raises the issue of creating alliances and sub-alliances that could ensure security issues in the Baltic countries and Eastern Europe as a whole. This, in turn, requires the definition of a new security system, built taking into account regional interests and new approaches to the system of collective provision of stable development. Global institutions in the context of new military conflicts show their inability to make decisions or their unwillingness to define new frameworks and conditions of security. Based on this, it seems important to form a new regional sub-alliance in Europe to ensure security and interpret the Trimoria alliance. The formation of military alliances leads to increased interaction between countries both in the military sector and in the economy as a whole. Within the alliances, a practically unified security system is formed, which works on the same standards, strengthening control over trade policy and forming a common control within the framework of military policy or security policy and protection from real or potential threats.